Understanding cashless payments in India - Bappaditya Mukhopadhyay (Financial Innovation, 2016)
Background: This paper analyzes India's gradual transition towards a cashless economy. Methods: We present a theoretical model that evaluates decisions by consumers and sellers to adopt cashless payments. We then use data from surveys conducted in 2011 and 2014 (from World Bank's Global Findex), as well as household and enterprise surveys conducted in 2009-2010 to estimate the amount of cashless transactions prevalent in India and identify the avenues that are successful and those that are not. We analyze instruments (cards versus point-of-sale versus mobile), micro units (individuals versus households versus retailers), and sectors to identify and estimate the enablers and bottlenecks. Results: We find that the most crucial enabler of cashless payments are inflows of funds into the accounts. Conclusion: Based on our findings, we suggest possible policy interventions.
Keywords: G18; G29; O53; 650; Cashless transactions; Survey; Network effect